ANALISA PENETAPAN KODE DIAGNOSIS UTAMA YANG AKURAT BERDASARKAN SPESIFIKASI PENULISAN PADA RESUME MEDIS RAWAT INAP DI RSU SUNDARI MEDAN - ROSALINA, YUDICA (LP2MTBM MAKARIOZ, 2023)
Sundari hospital Medan is a type C hospital, that has been used as guidelines ICD-10 for coding, the hospital had not conducted a study to determine the accuracy of the determination of primary diagnosis code based on specification writing primary diagnosis in the medical record document in the inpatient permata medika hospital 2020th periode. Rom the results of the initial survey using interviews with officers, inaccuracies in the coding of diagnosis were found on the medical resume of inpatients. This study used an observational method with a cross-sectional approach and the type of analytic research, while the population of this study amounted to 2,280 files of inpatient medical records for the 2020th periode so that a sample of 99 that are retrieved by using a random sample of sampling techniques. The results of the observations concluded that the main diagnosis code that was accurate from the specific diagnosis (Thypoid Fever) 54 (85,7%) was the main diagnosis code that was accurate from the non-specific diagnosis (Fever) 9 (14,3%), and the main diagnosis code was not accurate from specific diagnosis (Pneumonia) 14 (42.4%) the main diagnostic code was inaccurate from the non specific diagnosis (Effusion) 19 (57.6%). Conclusion obtained that is, to get the accuration of disease code, do not only influenced by writing diagnosed just specific especial, but influenced also by correctness of officer coding and also other factor which influencing in consequence officer koding better be active in searching information if finding diagnosed especial which is not specific and also need the existence of the make-up of knowledge of officer koding by joining in training of Coding ICD-10.